An uncommon history of common things, Volume 2 (National Geographic, 2015)
"This vivid, engrossing book reveals the fascinating stories behind the objects in your world, what you wear, what you eat, what entertains you, and more. Discover the history behind the world's tallest skyscrapers, find out when people first started drinking caffeine and why it wakes us up, and learn how GPS came to be,"--Amazon.com.